Revisiting Strategies for Maternal Health Care in the Face of COVID-19 Pandemic - Shrestha, N.; Dangal, G. (Kathmandu University Medical Journal, 2020)
Novel coronavirus (SARS-CoV-2) is a new strain of coronavirus causing COVID-19, first identified in Wuhan City, China towards the end of 2019. At present, there is no evidence that pregnant women are more likely to be severely ill, need ICU care, or die from the illness in comparison to non-pregnant adults. Evidences suggest that vertical transmission, might be possible. We searched and retrieved the published literature from PubMed and Google Scholar using various keywords. We further searched the official webpages of various organizations for the updated information. Pregnant individuals in particular are encouraged to take all available precautions to optimize health and avoid exposure to COVID-19. Adequate Testing should be prioritized in pregnant women admitted with suspected COVID-19. When a pregnancy is complicated by critical illness, the pregnant patient should ideally be cared for at a Level III or IV hospital. In the face of COVID-19, antenatal fetal surveillance and ultrasonography should continue as medically indicated when possible and elective ultrasound examinations should not be performed. Maternal immunizations continue to be an essential component of prenatal care and Ob-gyns should screen all pregnant individuals for mental health issues. Although the most commonly reported sign in COVID-19 is fever, nevertheless, other causes of intrapartum fever should not be overlooked. Cesarean delivery should be based on obstetric indications and not COVID-19 status alone. Infants born to patients with known COVID-19 should be considered infants with suspected COVID-19. The suspected or confirmed COVID-19 mother and infant can be allowed to remain together with enhanced precautions and suspected or confirmed maternal COVID-19 is not a contraindication to breastfeeding. If both the mother and the infant are healthy, it may be prudent to expedite discharge, so as to limit the risk of inadvertent exposure and infection. The Ob-gyns should commit to providing necessary care, although modifications to health care delivery approaches may be necessary.